ASATIDZUNA – Jurnal PGMI Vol. 07 No. 02 September 2025 - Mahmudin, Wildan; Mira Siti Sarah (Asatidzuna | Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The low level of active verbal participation among students is one of the problems that often occurs in Arabic language learning. This is due to the lack of learning media that are attractive to students. Flash cards in Arabic language learning are expected to attract students' attention to active verbal participation to help them master vocabulary in a fun and interactive way. This study aims to determine the implementation and obstacles of using flash cards in Arabic vocabulary learning, as well as to determine the active verbal participation skills of students in class IIB MI Nagarakasih 1. The method used is qualitative research. Data was collected through observation, interviews, and documentation. Data analysis techniques used the Miles and Huberman model, with the first stages being data collection, data reduction, data presentation, and conclusions. The results of this study indicate that flash cards encourage students' active verbal participation in mastering vocabulary in Arabic language learning. Students are enthusiastic about learning because the images on the flash cards make it easier to remember vocabulary. This enables students to review, memorize, and even translate vocabulary independently, without constant assistance from the teacher. Active participation is not only verbal engagement but also deep understanding and the ability to master the material independently.